2018
DOI: 10.1155/2018/4173520
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Experimental Studies on Preparation of Mine‐Filling Materials from Carbide Slag, Granulated Blast‐Furnace Slag, Fly Ash, and Flue‐Gas Desulphurisation Gypsum

Abstract: Environmentally friendly and cheap composite green cementitious materials have been prepared from carbide slag, fly ash, fluegas desulphurisation (FGD) gypsum, and granulated blast-furnace slag (GBFS) without using cement clinker. Orthogonal testing was used to investigate the effects of the raw materials on the amount of water required for reaching standard consistency and consistency, setting time, slump value, and strength of the produced materials after curing for 7 d and 28 d. Scanning electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…DGs also have more applications in filling materials. This study investigated environmentally friendly composite filling materials with calcium carbide slag (CCS), fly ash, granulated blast furnace slag, and DG, and used orthogonal tests to study the standard consistency of the water consumption of the raw materials [14], their setting time, and their strength; the results showed that as the DG content increased, the DG content among the raw materials increased. DG had the greatest influence on the standard weekly water consumption and setting time of the system.…”
Section: Filling Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…DGs also have more applications in filling materials. This study investigated environmentally friendly composite filling materials with calcium carbide slag (CCS), fly ash, granulated blast furnace slag, and DG, and used orthogonal tests to study the standard consistency of the water consumption of the raw materials [14], their setting time, and their strength; the results showed that as the DG content increased, the DG content among the raw materials increased. DG had the greatest influence on the standard weekly water consumption and setting time of the system.…”
Section: Filling Materialsmentioning
confidence: 99%
“…To increase the application of the industrial byproduct gypsum, it is necessary to develop low-cost and efficient decontamination and purification processes. Moreover, the application fields of gypsum byproducts, such as cementitious materials, road base materials, and mine filling materials, should be expanded, especially in the direction of larger application amounts [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…1) In recent years, international scholars [2][3][4] have conducted in-depth research on the modification of gypsum for its characteristics owing to its wide application in green building materials. Meanwhile, numerous scholars [5][6][7] have studied the modification of desulfurization of gypsum in order to improve the resource utilization value of the industrial by-product obtained during the desulfurization of gypsum.…”
Section: Introductionmentioning
confidence: 99%